Impact of frequent ARID1A mutations on protein stability provides insights into cancer pathogenesis - Rajen K. Goutam; Gangtong Huang; Exequiel Medina; Feng Ding; William J. Edenfield; Hugo Sanabria (Scientific Reports)
Abstract The ARID1A gene, frequently mutated in cancer, encodes the AT-rich interactive domain-containing protein 1 A, a key component of the chromatin remodeling SWI/SNF complex. The ARID1A protein features a conserved DNA-binding domain (ARID domain) of approximately 100 residues crucial for its function. Despite the frequency of mutations, the impact on ARID1A’s stability and contribution to cancer progression remains unclear. We analyzed five frequent missense mutations R1020S, M1022K, K1047Q, G1063V, and A1089T identified in The Cancer Genome Atlas (TCGA) to assess their effects on the stability of the ARID domain using a hybrid experimental and computational approach. By combining computational stability from web server tools, the structural dynamics from replica exchange discrete molecular simulation (rexDMD), and thermal and chemical denaturation experiments, we found that the R1020S mutation severely decreases structural stability, making it the most impactful, while M1022K has minimal effect, and others lie in between. These findings enhance our understanding of the structural-functional relationship of ARID1A missense mutations at the molecular levels and their role in cancer pathogenesis. This research paves the way for identifying and categorizing which ARID1A mutations are most pathogenic, potentially guiding the development of targeted therapies tailored to specific mutation profiles in cancer treatment.